The trichodysplasia spinulosa‐associated polyomavirus: virological background and clinical implications. Issue 8 (18th April 2013) - Kazem, Siamaque; van der, Els; Feltkamp, Mariet C. W.
<x xml:space="preserve">Abstract</x> Trichodysplasia spinulosa‐associated polyomavirus (TSPyV) is a new species of the family Polyomaviridae that was discovered in 2010. TSPyV infects humans and is associated with the development of a rare disease called trichodysplasia spinulosa. Trichodysplasia spinulosa is a skin disease of severely immunocompromised hosts characterized by follicular distention and keratotic spine formation especially on the face. Electron microscopy, immunohistochemistry, and viral load measurements indicate an etiological role of active TSPyV infection in the development of this disease. This review will address virological and pathogenic properties of TSPyV, as well as epidemiologic, diagnostic, and therapeutic aspects of TSPyV infection.